Pengembangan Praktikum Biologi di Sekolah Menengah Berbasis Etnobiologi - Sunariyati, Siti; Suatma, Suatma; Miranda, Yula (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Local knowledge of the Dayak Ngaju community in Gunung Mas regency, Central Kalimantan there were believed that many species of plants, animals and their surroundings can be used as an indicator of a particular environtment. The local people experience is one example of local knowledge which needs to be studied scientifically through ethnobiology. Study of ethnobiology was confined to the local community's knowledge about the medicinal plants (ethnobotany), local community knowledge about the utilization of existed nearby animals (ethnozoology) and knowledge of the local community in ecosystems around their living quarters (ethnoecology). Afterwards these studies was arranged into biology practical work material. The purposes of the study are (1) to study the ethnobiology of local knowledge of Dayak Ngaju communities in Gunung Mas regency, (2) to inventory and identify several species that are used in foodstuffs, pharmaceuticals, industry and utilization of the environment for the practical work in high school. Research activities consists of two phases, the first phase is the study of ethnobiological research by using qualitative approaches. Data was collected after observation and in-depth interviews. The second phase is the development of research by using Hannafin and Peck development model. The results showed that the Dayak Ngaju in Gunung Mas have local knowledge about the uses of plants, animals and their environment for food, industrial materials, pharmaceuticals and mining. This should be well documented and to be taught to the next generations to avoid the extinction of local knowledges. Integrating the material ethnobiology into learning biology is one of the best ways to deliver local knowledge in formal education. It was suggested to teach ethnobiology in biology practical work, especially in high school who have forest environment as characteristic of their territory since ethnobiological material was very important.